Prosthetic Rehabilitation of Nasal Defect: A Case Report - Ejlali, Masoud; Moghadam, Leila (Journal of Dental School, 2019)
Facial defects not only impact on the function and quality of life but also affect the psychological well-being and social behavior of patients. A nasal prosthesis can re-establish the esthetics and anatomical contour in patients with mid-facial defects, often more effectively than surgical reconstruction. For successful results, many factors such as retention, texture, color match and blending of tissue with the prosthesis must be taken into account. The aim of this clinical report was to describe a modified technique for rehabilitation of a nasal defect with suitable adaptation. This provisional prosthesis was made to restore the esthetic appearance of the patient with a mechanically retained design using a spectacle glass frame without inserting craniofacial implants.